1997
DOI: 10.1103/physrevb.56.2668
|View full text |Cite
|
Sign up to set email alerts
|

Growth and magnetic properties ofCoxNi1xandet al.

Abstract: We have grown ultrathin Co x Ni 1Ϫx and Fe x Ni 1Ϫx films on Cu͑100͒ with varying stochiometry x. We find that these alloy films grow in a fcc phase on Cu͑100͒. With the surface magneto-optic Kerr effect we measured the variation of the Curie temperature T C as a function of the film thickness n in monolayers. Fitting an empirical scaling curve to our results we are able to extrapolate the value T C (nϭϱ) for samples with different stochiometry. We use this framework in order to determine T C (nϭϱ) for Fe x Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 50 publications
4
22
0
Order By: Relevance
“…[4][5][6][7][8] The focus of this work is Fe-based alloys, which can be prepared in a fcc phase throughout the whole concentration regime. 9,10 This contrasts the behavior of the bulk, where a bcc phase is adopted for Fe-rich alloys. In this work we will use magnetic linear dichroism in angleresolved photoemission with linear polarized light ͑MLDAD͒.…”
Section: Introductionmentioning
confidence: 95%
“…[4][5][6][7][8] The focus of this work is Fe-based alloys, which can be prepared in a fcc phase throughout the whole concentration regime. 9,10 This contrasts the behavior of the bulk, where a bcc phase is adopted for Fe-rich alloys. In this work we will use magnetic linear dichroism in angleresolved photoemission with linear polarized light ͑MLDAD͒.…”
Section: Introductionmentioning
confidence: 95%
“…The quadratic dispersion constant of spin waves at small wave vector 41 (ϳ2JS) and the magnetic moments (ϳg s B S) were used to calculate J Ni,Ni ͉S Ni ͉ 2 ϭ51 K and J Fe,Fe ͉S Fe ͉ 2 ϭ218 K. An approximate value for J Ni,Fe S Ni •S Fe is found by scaling J Ni,Ni ͉S Ni ͉ 2 by the ratio of T c for ultrathin equal concentration FeNi alloy films and Ni films. 42 For layered and mixed films, an average exchange can be defined as…”
Section: ͑13͒mentioning
confidence: 99%
“…14,15 This allowed us to investigate the electronic properties of these alloys with changing composition independent of any change in their lattice structure. All films were grown to a thickness of 8 ML to avoid any contribution from the electronic structure of the Cu substrate.…”
Section: A Fermi Surfaces Of Pseudomorphic Fcc Films On Cu"100…mentioning
confidence: 99%
“…12,13 It has been demonstrated that it is possible to grow ultrathin fcc Co 1Ϫx Ni x alloy films epitaxially on Cu͑100͒ with variable stoichiometry. 14,15 For Co 1Ϫx Ni x alloy films, the fcc phase is adopted in the whole concentration range and the magnetic moment varies linearly between the values of Ni and Co, while the Curie temperature remains a monotonic function of the composition. The lattice of pseudomorphic fcc Co x Ni 1Ϫx alloy films remains constant throughout the whole concentration range.…”
Section: Introductionmentioning
confidence: 99%